ICTV Virus Taxonomy Profile: Bornaviridae - Rubbenstroth, Dennis; Briese, Thomas; Dürrwald, Ralf; Horie (堀江真行), Masayuki; Hyndman, Timothy H.; Kuhn, Jens H.; Nowotny, Norbert; Payne, Susan; Stenglein, Mark D.; Tomonaga (朝長啓造), Keizō (Journal of general virology, 2021)
Members of the family Bornaviridae produce enveloped virions containing a linear negative-sense non-segmented RNA genome of about 9 kb. Bornaviruses are found in mammals, birds, reptiles and fish. The most-studied viruses with public health and veterinary impact are Borna disease virus 1 and variegated squirrel bornavirus 1, both of which cause fatal encephalitis in humans. Several orthobornaviruses cause neurological and intestinal disorders in birds, mostly parrots. Endogenous bornavirus-like sequences occur in the genomes of various animals. This is a summary of the International Committee on Taxonomy of Viruses (ICTV) Report on the family Bornaviridae , which is available at ictv.global/report/bornaviridae .